2017
DOI: 10.1177/0218492317731389
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of different methods of esophagectomy for esophageal cancer

Abstract: Background A minimally invasive approach to esophagectomy is being used increasingly, but concerns remain regarding the feasibility, safety, cost, and outcomes. We performed an analysis of the costs and benefits of minimally invasive, hybrid, and open esophagectomy approaches for esophageal cancer surgery. Methods The data of 83 consecutive patients who underwent a McKeown's esophagectomy at Prince of Songkla University Hospital between January 2008 and December 2014 were analyzed. Open esophagectomy was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The review identified 98 studies 6,7,34–129 comparing surgical approaches for oesophagectomy, involving 32 315 patients ( Fig . 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The review identified 98 studies 6,7,34–129 comparing surgical approaches for oesophagectomy, involving 32 315 patients ( Fig . 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 studies, including 2 RCTs[8,9] and 15 case-control studies[10-24], were eligible for the meta-analysis. The studies included 2397 esophageal carcinoma patients, of which 1170 received HMIE and 1227 underwent OE.…”
Section: Resultsmentioning
confidence: 99%
“…Smithers et al[12] reported that patients who underwent HMIE had less blood loss than those undergoing OE, while Yanasoot et al[24] showed no significant difference. In our meta-analysis also, the total HMIE group and the HMIE with laparoscopy and thoracotomy group had less blood loss, which could be attributed to the relatively minimal trauma in HMIE.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer is the eighth most common cancer worldwide and the overall prognosis for patients is still poor . While esophageal adenocarcinoma has emerged as the major histological subtype in Western countries, squamous cell carcinoma is the more common histology in certain geographic areas, including Brazil, northern China, Iran, Russia, and South Africa .…”
Section: Introductionmentioning
confidence: 99%